Nativos digitais na sociedade tecnológica: desafios para o século XXI - Gobbi, Maria Cristina [UNESP] (My University, 2012)
Youth have always organized various movements for social transformation. Utopian or radical of these activities have enabled significant changes in political and social structures in various sectors and on different continents. The text is intended to check what causes the connections between youth and technological society, observing the connections between them. Using literature review, we try to recognize the culture, media and technologies around which these groups are related, they express and consider their representative in the development of communicative identity.

Os jovens sempre protagonizaram diversos movimentos de transformação social. Utópicas ou radicais essas atividades têm possibilitado mudanças significativas nas estruturas políticas e sociais de diversos setores e nos variados continentes. O texto objetiva verificar como ocorrem as conexões entre a juventude e a sociedade tecnológica, observando as articulações entre eles. Utilizando pesquisa bibliográfica, buscamos reconhecer a cultura, mídias e tecnologias em torno das quais esses grupos se articulam, se expressam e quais consideram representativa na elaboração de sua identidade comunicativa.
Keywords: Juventude; Televisão digital; Tecnologias digitais